Platelets tune fear memory in mice - Stefano Garofalo; Alessandro Mormino; Letizia Mazzarella; Germana Cocozza; Arianna Rinaldi; Erika Di Pietro; Maria Amalia Di Castro; Eleonora De Felice; Laura Maggi; Giuseppina Chece; Diego Andolina; Rossella Ventura; et al. (Cell Reports)
Summary: Several lines of evidence have shown that platelet-derived factors are key molecules in brain-body communication in pathological conditions. Here, we identify platelets as key actors in the modulation of fear behaviors in mice through the control of inhibitory neurotransmission and plasticity in the hippocampus. Interfering with platelet number or activation reduces hippocampal serotonin (5-HT) and modulates fear learning and memory in mice, and this effect is reversed by serotonin replacement by serotonin precursor (5-HTP)/benserazide. In addition, we unravel that natural killer (NK) cells participate in this mechanism, regulating interleukin-13 (IL-13) levels in the gut, with effects on serotonin production by enterochromaffin cells and uptake by platelets. Both NK cells and platelet depletion reduce the activation of hippocampal inhibitory neurons and increase the long-term potentiation of synaptic transmission. Understanding the role of platelets in the modulation of neuro-immune interactions offers additional tools for the definition of the molecular and cellular elements involved in the growing field of brain-body communication.